Solvent Retention of Contemporary Commercial Dentin Bonding Agents in a Demineralized Dentin Matrix - Garcia, Georges; Parron Fernandes, Karen Barros; Pimentel Garcia, Fernanda Cristina; Perlatti D’Alpino, Paulo Henrique; Svizero, Nádia da Rocha; Wang, Linda (European Journal of Dentistry, 2010)
Objectives: Solvents are ingredients in dentin-bonding agents (DBAs) that are essential to obtain efficient adhesion to dentin under wet-technique bonding protocol. However, an excess of solvents can compromise bonding durability. This study aimed to assess the retention of solvents present in different DBAs after their application to a demineralized dentin matrix.Methods: Thirty-six specimens of bovine dentin were demineralized for 7 days in 0.5M EDTA and divided into six groups n=6 (Scotchbond primer, Adper Single Bond 2, Excite, AdheSE primer, Prime & Bond NT and Xeno III). These specimens were individually saturated by the systems for 5 min and then kept in vials protected against light exposure. Each specimen was measured using a digital balance and then measured at the following intervals 10, 20, 30 sec, 1, 2 and 5 min thereafter. Data were analyzed by two-way ANOVA and Tukey tests (alfa=.05).Results: There were significant differences evident in Excite, Prime & Bond NT at 2 and 5 min, respectively. There was no significant interaction between materials and time in all experimented time evaluated. The amount of solvent spontaneously evaporated was limited even in acetone-based specimens.Conclusions: After DBAs are applied, professionals may facilitate their evaporation, since spontaneous evaporation is limited. (Eur J Dent 2010;4:293-297)
Keywords: Solvents; Dentin-bonding systems; Dentin; Evaporation